Morphological, Molecular and Toxicology of Pseudo-nitzschia cuspidata and Alexandrium pseudogonyaulax with Descriptions of Two New Alexandrium Species in Selected Malaysian Waters - NURSYAHIDA, ABDULLAH (Universiti Malaysia Sarawak, (UNIMAS), 2023)
Pseudo-nitzschia and Alexandrium are harmful algal blooms (HAB) genera that commonly found in the Malaysian waters. Both genera were reported as toxic species and associate with the shellfish contamination in the Southeast Asia region. Pseudo-nitzschia is a worldwide pennate diatom that is known to contain domoic acid (DA) and cause amnesic shellfish poisoning (ASP). On the other hand, Alexandrium pseudogonyaulax is one of the toxins goniodomin producer from the dinoflagellate group. These potent antifungal toxins associated to aquatic invertebrate mortalities. The objectives of this study were to investigate the potential toxic of Pseudo-nitzschia in environmental condition and taxonomic study of A. pseudogonyaulax in Malaysian waters. In March 2018, a Pseudo-nitzschia algal bloom was discovered for the first time in Miri, Sarawak, Malaysia Borneo. The plankton samples were collected for cell enumeration and species identification by electron microscopic and molecular characterisation. The neurotoxic domoic acid (DA) was detected and quantified in both plankton and shellfish samples using liquid chromatography-mass spectrometry (LC-MS/MS). The abundance of Pseudo-nitzschia cells was found in the range of 5.6 × 105 to 3.5 × 106 cell L-1 during the bloom event. Morphological observation of the cells by transmission electron microscopy showed that the plankton samples comprised a single Pseudo-nitzschia morphotype resembled P. cuspidata. The ITS2 sequence-structure phylogenetic inference further supported the species identify as P. cuspidata. DA was detected in the plankton samples, with cellular DA, particulate DA, and dissolved DA of 257–504 fg DA cell-1, 676 ng/L, and 15 ng/L, respectively. The amount of DA, 8 μg g-1 tissue, was found present in the oyster sample (Crassostrea). Dinoflagellate Alexandrium pseudogonyaulax from the subgenus Gessnerium is one of the goniodomin. The subgenus Gessnerium possesses common thecal characteristics like indirect connection of first apical (1') plate to the apical pore complex (Po) and oblique posterior sulcal plate (Sa). The group species identification is relied on the minute differences in the shape of the 1' and 6'' plates. Seven strains of Alexandrium-like cell were established in this study. All the clonal cultures were undergone microscopic observation and molecular characterisation. A. pseudogonyaulax was identified and two new morphotypes, herein designated as Alexandrium limii nom. nud. and Alexandrium ogatae nom. nud. Alexandrium limii differs from A. taylorii in length of the suture and 1', 6'', Sa and position of ventral pore. Alexandrium ogatae differs from A. foedum by the shape of plate 1', 6'', 2'''', and Sp. The species delineations were further supported by the phylogenetic inferences using two ribosomal gene markers, i.e., the large subunit (LSU) rDNA and internal transcribed spacer (ITS), including the complementary base changes (CBCs) analysis. The results showed A. limii and A. ogatae were clustered together with A. pseudogonyaulax, A. taylorii, and A. hiranoi. The species lineages were also supported by high genetic divergences. The pairwise comparisons of the ITS2 transcripts revealed the presence of CBCs between the A. limii and A. ogatae with the closely related species. This is first time for Pseudo-nitzschia cuspidata bloom in Southeast Asia, and it has been connected to shellfish domoic acid pollution. This study also documented for the first time of subgenus Gessnerium in Malaysia water based on the detail morphology and molecular with description of the two new species.